Influence of elastic characteristics of raw cotton on the mechanics of feed rollers in the cleaners from large impurities - Veliev, Fazil; Sailov, Rahib (Eastern-European Journal of Enterprise Technologies, 2018)
The impact of harvesting time on the quality of raw cotton, as well as on the physical-mechanical properties of the fiber, is of paramount importance, as the cotton’s maturity and content of impurities affect the quality of cleaning cotton from impurities. Our experimental study was carried out under actual field conditions. Research results have confirmed that harvesting time significantly affects the maturity and quality of raw cotton. It was established that more than 60 % of the raw cotton, harvested at the cotton boll opening from 50 % to 60 %, meet the requirements of the first industrial grade, that is, the fiber breaking load exceeds 4.5 cN. Given the fact that mature raw cotton deforms well, it leads to the enhanced cleaning effect. The result of theoretical research is the established spreading efforts during deformation of a cotton layer by the cleaner’s blades and the analyzed shapes of the deformed layer of cotton. We estimated the elastic characteristics of raw cotton and calculated spreading efforts. To determine the numerical values for the pressure forces at which a blade acts on the flow of raw cotton, for a coefficient K of the generalized properties of a material, the magnitude V for raw cotton was adopted in a range of 0.25‒0.3. Experiments have shown that a layer of raw cotton with a thickness from 170 to 380 mm and a width of 700 mm was loaded with the force of 3‒10 kgf concentrated along the line. Based on our calculations, it was established that 38.89 % of the raw cotton cleaning time accounts for the operation of a single blade of the roller. The result of our experimental and theoretical research is the data that make it possible to organize effective operation of cleaning machines in the cotton cleaning industry.